2019
DOI: 10.14202/vetworld.2019.527-534
|View full text |Cite
|
Sign up to set email alerts
|

Identification and dietary exposure assessment of tetracycline and penicillin residues in fluid milk, yogurt, and labneh: A cross-sectional study in Lebanon

Abstract: Background and Aim: The safety and quality of dairy products are considered to be of significant importance to human health. Although antimicrobial drugs are essential for disease treatment in modern medicine, the use of these drugs can have undesired consequences for human and animal health. This study aimed to investigate the presence of tetracycline and penicillin residues in raw, pasteurized, and UHT cow's milk of different fat contents, as well as in the dairy products yogurt and labneh, a traditional Leb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…To the best of our knowledge, there has been a lack of comprehensive data concerning Lebanese exposure to antibiotic from clinical use and residues in foods. Only one study revealed that penicillin and tetracycline residues in dairy products marketed in Lebanon were below the maximum residue limits (MRLs) [28].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there has been a lack of comprehensive data concerning Lebanese exposure to antibiotic from clinical use and residues in foods. Only one study revealed that penicillin and tetracycline residues in dairy products marketed in Lebanon were below the maximum residue limits (MRLs) [28].…”
Section: Introductionmentioning
confidence: 99%
“…That is why it is important to monitor the concentration levels of antibiotic residues in animals and in food products of animal origin [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Studies on the quantitative risk assessment of foods provide important frameworks to address some of the issues related to the risk to human health from the intake of various residues via food [ 32 , 33 , 34 , 35 , 36 ]. Recently, a study on the residue concentrations and exposure levels of ethoxyquin and ethoxyquin dimer in farmed aquatic animals in Korea has been published [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in several countries have highlighted the level of risk faced by populations consuming food of animal origin containing antibiotic residues ( 15 17 ). For example, in Lebanon, the risks due to tetracycline and penicillin residue intake from all dairy products were estimated at 0.007 and 0.006%, respectively ( 18 ). Bou-Mitri et al ( 19 ) from their study in the same country found that the dietary exposure to penicillin through meat consumption was equivalent to 88.3, 31.9, and 5.7% of the acceptable daily intake (ADI), using Tiers 1, 2, and 3 approaches, respectively.…”
Section: Introductionmentioning
confidence: 99%